BEYOND STANDARD RISK FACTORS: THE GENETIC AND ANAMNESTIC PROFILE OF PATIENTS WITH SEVERE PREECLAMPSIA IN THE UZBEK POPULATION (World Bulletin of Social Sciences, 2025)
To analyze the clinical-demographic characteristics, latent risk factors, and genetic predictors of severe preeclampsia (PE) as a form of secondary thrombotic microangiopathy (TMA)